Analysis of Financial Statements and Cash Flow Statements in Assessing Financial Performance at Health Social Security Administering Agency (BPJS) for the Period 2021 - 2023 - Ferinluary, Fadila; Rahayu, Sri; Arum, Enggar Diah Puspa; Wiralestari, Wiralestari (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to analyze the financial performance of the Health Social Security Administering Agency (BPJS) for the 2021-2023 period when viewed from financial ratio analysis and cash flow ratio analysis. This type of research is descriptive research with a quantitative approach. This research uses financial ratio analysis techniques and cash flow ratios in a time series. Financial ratio analysis can be used as a reference for a company's development to assess how well its financial performance is. The variables used are the liquidity ratio consisting of the current ratio, the solvency ratio consisting of the debt to asset ratio, and the profitability ratio consisting of return on assets and return on equity. Apart from analyzing the company's balance sheet and profit and loss financial statements, in assessing financial performance there is one more report that can be assessed, namely through the cash flow report. The cash flow ratio analysis used is the operating cash flow ratio, capital expenditure ratio and total debt ratio. The results of this research show that BPJS Health's financial performance for the 2021-2023 period shows good liquidity and solvency, but profitability and cash flow management are still weak due to significant losses in 2022 and 2023. Strategy improvements are needed to increase efficiency and financial sustainability.